A report on SARS-CoV-2 first wave in Ecuador: drug consumption dynamics - Orellana-Manzano, Andrea; Cordeiro, Fernanda B.; Garcia-Angulo, Andrea; Centeno, Elizabeth; Vizcaíno-Tumbaco, María José; Poveda, Sebastián; Murillo, Ricardo; Andrade-Molina, Derly; Mirabá, Mariuxi; Mehta, Saurabh; Cárdenas, Washington (Frontiers in Pharmacology, 2023)
Introduction: The first COVID-19 wave in Ecuador started in March 2020 and extended until November. Several types of drugs have been proposed as a potential treatment during this period, and some affected people have self-medicated. Method: A retrospective study was conducted with 10,175 individuals who underwent RT-PCR tests for SARS-CoV-2 from July to November 2020. We compared the number of positive and negative cases in Ecuador with symptoms and drug consumption. The Chi-square test of independence compared clinical and demographic data and PCR test results. Odds ratios analyzed drug consumption dynamics. Results: Of 10,175 cases, 570 were positive for COVID-19, while 9,605 were negative. In positive cases, there was no association between the RT-PCR result and sex, age, or comorbidities. When considering demographic data, Cotopaxi and Napo had the highest rates of positive cases (25.7% and 18.8%, respectively). Manabí, Santa Elena, and Guayas regions had fewer than 10% positive cases. The Drug consumption dynamic analysis showed that negative COVID-19 cases presented higher drug consumption than positive cases. In both groups, the most consumed medication was acetaminophen. Acetaminophen and Antihistamines had higher odds of consumption in positive PCR cases than in negative. Symptoms like fever and cough were more related to positive RT-PCR results. Conclusion: The first COVID-19 wave in Ecuador has affected the provinces differently. At a national level, the consumption of drugs has been highly associated with self-medication.